Experimental study on growth characteristics of pore-scale methane hydrate - Zhan-dong Li; Xin Tian; Zhong Li; Jin-ze Xu; Hai-xiang Zhang; Dian-ju Wang (Energy Reports, 2020)
In order to study the behavioral characteristics of the pore-scale hydrate formation, this experiment employs a high-pressure-resistant visible model in an etched glass plate to study the pore-scale methane hydrate formation and reveal its growth law s in porous media. The experiment shows that the evolution of natural gas hydrates is divided into three periods, namely, the instability period of gas-liquid dissolution, the hydrate growth period, and the hydrate formation period. The hydrate growth process accelerates when pressure increases. The increase in temperature yields a random trend. The hydrate growth period has three substages: the gas-liquid cluster and nucleation stage, the gas-liquid film formation and accretion stage, and the deposition and crystallization stage. The hydrate growth laws are drawn as follow: (1) The nucleation characteristics of the gas hydrate directly determine the hydrate's spatial distribution in the pores. The heterogeneous nucleation is more likely to occur. (2) The spatiotemporal growth of the hydrates is an interaction of two kinds of transformations in the porous media, namely, the transformation from the disordered to the ordered, and the transformation from the hydrophobic to the hydrophilic. In the early stage, the gas-liquid contact appears to be hydrophobic, and the gas-liquid dissolution process shows a repeated disorder. In the later stage, the hydrate begins to be "hydrophilic", which means it follows the existing hydrate interface to grow orderly into the depth of the pores. (3) The geometric distribution of the pore structure can change the spatial structure of the water molecules' growth, which leads the hydrate to distribute with a geometric anisotropy. The research results are aimed to provide a theoretical basis for the exploitation and optimization of marine natural gas hydrates.
Keywords: 330; Gas hydrates; Heterogeneous nucleation; Methane; Nucleation and growth; Pore scale; Visualization